2016
DOI: 10.1002/ijop.12375
|View full text |Cite
|
Sign up to set email alerts
|

Perception of mind and dehumanization: Human, animal, or machine?

Abstract: Dehumanization is reached through several approaches, including the attribute-based model of mind perception and the metaphor-based model of dehumanization. We performed two studies to find different (de)humanized images for three targets: Professional people, Evil people, and Lowest of the low. In Study 1, we examined dimensions of mind, expecting the last two categories to be dehumanized through denial of agency (Lowest of the low) or experience (Evil people), compared with humanized targets (Professional pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…The first set comprised of six questions to which participants were asked to answer indicating their agreement on a 7-point Likert-type scale (see Appendix 1). The items were adapted from Morena et al’s (2016) study, which is itself based on Gray et al’s (2007, 2011) dimensions of mind perception. This model evaluates ‘humanness and its opposite, dehumanization’ (Morena et al, 2016: 1) – defined as ‘denying other people mental capacities’ (Morena et al, 2016: 2) – and ‘investigate[s] whether people negate distinct abilities (agency and experience) of the mind’ (Morena et al, 2016: 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first set comprised of six questions to which participants were asked to answer indicating their agreement on a 7-point Likert-type scale (see Appendix 1). The items were adapted from Morena et al’s (2016) study, which is itself based on Gray et al’s (2007, 2011) dimensions of mind perception. This model evaluates ‘humanness and its opposite, dehumanization’ (Morena et al, 2016: 1) – defined as ‘denying other people mental capacities’ (Morena et al, 2016: 2) – and ‘investigate[s] whether people negate distinct abilities (agency and experience) of the mind’ (Morena et al, 2016: 2).…”
Section: Methodsmentioning
confidence: 99%
“…The items were adapted from Morena et al’s (2016) study, which is itself based on Gray et al’s (2007, 2011) dimensions of mind perception. This model evaluates ‘humanness and its opposite, dehumanization’ (Morena et al, 2016: 1) – defined as ‘denying other people mental capacities’ (Morena et al, 2016: 2) – and ‘investigate[s] whether people negate distinct abilities (agency and experience) of the mind’ (Morena et al, 2016: 2). The first three questions measure perception of agency (capacity of self-control, capacity to act morally, capacity to plan), while the last three questions measure perception of experience (capacity to experience emotion, capacity to experience refined or uniquely human feelings, capacity to experience consciousness).…”
Section: Methodsmentioning
confidence: 99%
“…Some notable examples from film would be the robot assassin in "The Terminator," the soulless, visored Teutonic knights in Eisenstein's film "Alexander Nevsky," or the mechanistic imagery surrounding the emotionless Soviet boxer Ivan Drago in "Rocky IV." Recent evidence has found that evil persons, such as terrorists or mercenaries, can elicit mechanistic as well as animalistic dehumanization (Morera et al, 2018). The authors argue that this is because evil persons can be simultaneously seen as capable and also savagelike.…”
Section: Animalistic Versus Mechanistic Dehumanizationmentioning
confidence: 99%
“…The intent to harm also implies that the harmdoer is animalistic, lacking reflection or moral feelings that would restrain the commission of violence. Indeed, evil people who threaten harm are viewed with metaphors of animalistic dehumanization (Morera, Quiles, Correa, Delgado & Leyens, 2018). So, if fear is related to animalistic dehumanization of a group, this might be because the group is seen as morally deficient and evil, like an animal that preys on humans.…”
Section: Why Fear?mentioning
confidence: 99%
“…Previous research has found that when women are sexualized, they are also often dehumanized (Bernard et al, 2015;Puvia & Vaes, 2013Vaes, Paladino, & Puvia, 2011). One cause of dehumanization is a lack of perceived agency (Lebowitz & Ahn, 2016;Li, Leidner, & Castano, 2014;Morera, Quiles, Correa, Delgado, & Leyens, 2016;Tipler & Ruscher, 2014). Furthermore, perceived agency and humanness of women are known to mediate the relationship between exposure to sexual media and sexually aggressive attitudes (Blake, Bastian, & Denson, 2016;Rudman & Mescher, 2012).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%